2022
DOI: 10.18043/ncm.83.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Receipt of Contraceptives by Insurance Status and Race/Ethnicity

Abstract: D espite decreases in unintended pregnancies over the past decade, more than half of pregnancies among US women aged 18-29 are unplanned [1]. At 51%, the US unintended pregnancy rate is substantially higher than that of most European countries [2], with costs estimated at $21 billion in 2010 [3]. Unplanned pregnancies are associated with poorer outcomes including delayed or inadequate prenatal care, increased levels of stress and depression, and decreased rates of breastfeeding among mothers [4-6], and prematu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…It is clear through multiple studies that socioeconomic status and race overlap and may compound barriers to care that patients of minority racial and ethnic backgrounds may face. For example, one study found that compared to White women with commercial insurance, Black and Hispanic women with Medicaid had higher odds of receiving LARC, suggesting implicit biases that may influence contraception counseling [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is clear through multiple studies that socioeconomic status and race overlap and may compound barriers to care that patients of minority racial and ethnic backgrounds may face. For example, one study found that compared to White women with commercial insurance, Black and Hispanic women with Medicaid had higher odds of receiving LARC, suggesting implicit biases that may influence contraception counseling [ 15 ].…”
Section: Discussionmentioning
confidence: 99%